Effectiveness of a Gamification Strategy to Prevent Childhood Obesity in Schools: A Cluster Controlled Trial - Villalobos-Dintrans, P (John Wiley and Sons Inc, 2021)
Objective: The aim of this study was to examine the effectiveness of a school-based gamification strategy to prevent childhood obesity. Methods: Schools were randomized in Santiago, Chile, between March and May 2018 to control or to receive a nutrition and physical activity intervention using a gamification strategy (i.e., the use of points, levels, and rewards) to achieve healthy challenges. The intervention was delivered for 7 months and participants were assessed at 4 and 7 months. Primary outcomes were mean difference in BMI z score and waist circumference (WC) between trial arms at 7 months. Secondary outcomes were mean difference in BMI and systolic and diastolic blood pressure between trial arms at 7 months. Results: A total of 24 schools (5 controls) and 2,197 students (653 controls) were analyzed. Mean BMI z score was lower in the intervention arm compared with control (adjusted mean difference −0.133, 95% CI: −0.25 to −0.01), whereas no evidence of reduction in WC was found. Mean BMI and systolic blood pressure were lower in the intervention arm compared with control. No evidence of reduction in diastolic blood pressure was found. Conclusions: The multicomponent intervention was effective in preventing obesity but not in reducing WC. Gamification is a potentially powerful tool to increase the effectiveness of school-based interventions to prevent obesity. © 2021 The Authors. Obesity published by Wiley Periodicals LLC on behalf of The Obesity Society (TOS).